Market for information and selling mechanisms - David Bounie; Antoine Dubus; Patrick Waelbroeck (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
A monopolist data intermediary collects consumer information that it strategically sells to competing firms in a product market for price discrimination purposes. The intermediary charges a price of information and chooses the optimal partition that maximizes the willingness to pay of firms for information. Different selling mechanisms are compared: list prices, sequential bargaining, and auctions. The intermediary optimally sells information through auctions, whereas consumer surplus is maximized with sequential bargaining and list prices. We discuss the regulatory implications of our results.
Keywords: 330; Selling mechanisms; Market for information; Data intermediaries; Competition policy; Regulation of digital markets